Mass transfer between mudstone-sandstone interbeds during diagenesis as revealed from the type and distribution of carbonate cements in the Eocene beach-bar sandstones, Bohai Bay Basin. (December 2019) - Wang, Jian; Cao, Yingchang; Liu, Keyu; Wang, Xintong; Xiao, Jie; Xie, Ning
Abstract: The characteristics, heterogeneous distribution and origins of carbonate cements within beach-bar sandstones in the Boxing Sag and implications on the mass transfer from mudstone to sandstone during diagenetic process was investigated systematically by an integrated analysis invoking petrography, carbon and oxygen stable isotopes and porosity-permeability, with specific references to the contrasts among the sharp (S)-change lithology (S-mudstone-S-sandstone interbeds), the gradual (G) -change lithology (G-mudstone-G-sandstone interbeds) and the center of sandstones. There are distinct differences in the occurrence, content, distribution, carbon and oxygen isotopic compositions and precipitation temperatures of the carbonate cements among the S-sandstone, G-sandstone and center of sandstone. Material sources of carbonate cements in the S-sandstones are mainly derived from the diagenetic alterations of the nearby S-mudstones through mass transfer with the participation of organic CO2, while in the G-sandstones, the material sources are mainly internal and originated from the calcareous matrix. Dissolution of feldspars and conversion of clay minerals provided the main materials for the precipitation of carbonate cements in the center of sandstones. Mass transfer of carbonate cements mainly occurred between the S-mudstones and the S-sandstones with limited transmission distance, which controlled the distribution of carbonate cements in the S-mudstones. There was almost no mass transfer between the G-mudstones and G-sandstones because of the small concentration gradient, instead, the depositional components and recrystallization controlled the carbonate distribution of the G-sandstones. Highlights: Material sources of carbonates in S-sandstones were mainly from nearby S-mudstones. Material sources of carbonates in G-sandstones were mainly from in situ recrystallization. Mass transfer of carbonate cements mainly occurred through sharp contact between mudstone and sandstone.